Persepsi Anggota Dewan Perwakilan Rakyat Daerah (DPRD) Kota Depok Terhadap Pembangunan Kesehatan di Depok Tahun 2018 - Susilawati; Andri Yan; Susilawati (UHAMKA Press, 2019)
ABSTRACT This study aims to explore perceptions of the main health problems in Depok according to members of the Depok Regional House of Representatives (DPRD) and the Head of Depok City Health Office. This research uses qualitative methods with descriptive research design. The research subjects were seventeen Depok DPRD members. Data collection techniques used in this research are observation, interviews, and documentation. Data reduction, data presentation and data verification were used in data analysis process. Triangulation of techniques and sources have been performed. The Informants stated several main problems in Depok City which are inadequate number of health service facilities and the infrastructures, unhealthy behavior, inequitable access to health Care by the poor in community, lack of health workers, the existence of infectious and non-communicable diseases, limited collaboration between the government and private sector specifically in national health insurance scheme, environmental health issues , drug abuse and lack of performance of information management systems especially at the Regional General Hospital. Keywords: Perception, Regional House of Representatives, Health Development, Health Problem